PSYCHODERMATOLOGY – FOCUS ON PSYCHIATRIC OUTCOMES OF THERMAL SKIN INJURIES - Simic, Marko; Velickovic, Uros (Medicinski časopis, 2025)
Psychodermatology represents the discipline that explores the complex interaction between the central nervous system and the skin and offers a lot of confirmations for bidirectional interconnection between the pathological alterations that affect both the skin and nervous system. Psychodermatological disorders can be classified into three principal groups: Psychophysiological disorders, Psychiatric disorders with dermatological symptoms, and Dermatological disorders with psychiatric symptoms, while other entities that appear in clinical practice are classified as Miscellaneous. Thermal skin injuries are classified in the category of dermatitis artefacta. It has been confirmed that burns do not affect somatic health components only, but also have a deep impact on the patient’s mental health and overall quality of life. Severe thermal skin injuries have been shown to also exert a significant systemic response that is finally accompanied by a visible impact on mental health. The major groups of markers that show the common type of alterations that connect cutaneous events (typical for thermal injury) and mental outcomes accompanied by burns are oxidative stress and inflammation markers, neurotransmitters, and neurotrophin system elements. The aim of this literature overview was to summarize some specific clinical entities for psychiatric/dermatological disorders that share the same underlying pathophysiological mechanisms, especially from the rarely evaluated direction (“skin to brain”) – psychiatric outcomes of thermal skin injuries.